Depletion of gut secretory immunoglobulin A coated Lactobacillus reuteri is associated with gestational diabetes mellitus-related intestinal mucosal barrier damage. Issue 21 (5th October 2021) - Zhang, Haowen; Qi, Ce; Zhao, Yuning; Lu, Mengyao; Li, Xinyue; Zhou, Jingbo; Dang, Hongyang; Cui, Mengjun; Miao, Tingting; Sun, Jin; Li, Duo
Abstract : Gestational diabetes mellitus (GDM) may be related to intestinal mucosal damage and inflammation-induced dysbiosis of secretory IgA (SIgA) coated microbiota. SIgA coated L. reuteri can reduce the level of inflammation of GDM in vitro . Abstract : Changes in secretory immunoglobulin A (SIgA) coated bacteria from early to late pregnancy were associated with the development of gestational diabetes mellitus (GDM). SIgA coated beneficial gut bacteria, which are depleted in GDM, are potential probiotics for the prevention of GDM. We investigated blood biochemistry, chronic inflammation, mucosal barrier biomarkers and faecal SIgA coated microbiota in healthy early pregnancy (T1H, n = 50), late pregnancy (T3H, n = 30) and women with GDM (T3D, n = 27). The "leaky gut" markers, zonulin and lipopolysaccharide (LPS), significantly increased in T3D compared to the T3H group. The Shannon index of SIgA coated microbiota was elevated in late pregnancy compared to early pregnancy and was the highest in the T3D group ( p < 0.001). The T3D group was enriched in SIgA coated Escherichia and Streptococcus and depleted in Lactobacillus and Bifidobacterium . Blood glucose (BG) positively correlated with zonulin ( p < 0.001) and LPS ( p < 0.05). Lactobacillus reuteri negatively correlated with BG ( p < 0.05), zonulin ( p < 0.05) and LPS ( p < 0.01). Lactobacillus reuteri QS01 isolated from the feces of T1H significantly reduced LPS released by the gut microbiota of GDM individuals in vitro . In conclusion, GDM may be related to intestinal mucosal damage and inflammation-induced dysbiosis of SIgA coated microbiota. SIgA coated L. reuteri can reduce the level of LPS of GDM in vitro .